Bài 1: Căn bậc hai

Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
thienphong lanhchan

\(\sqrt{7-4\sqrt{3}}+\sqrt{13-4\sqrt{3}}\)

Nguyễn Thị Diễm Quỳnh
12 tháng 10 2019 lúc 18:23

\(\sqrt{7-4\sqrt{3}}+\sqrt{13-4\sqrt{3}}=\sqrt{\left(\sqrt{3}-1\right)^2}+\sqrt{\left(2\sqrt{3}-1\right)^2}=\left|\sqrt{3}-1\right|+\left|2\sqrt{3}-1\right|\)

\(=\sqrt{3}-1+2\sqrt{3}-1=3\sqrt{3}-2\)

Lê Thu Dương
12 tháng 10 2019 lúc 18:40

\(\sqrt{7-4\sqrt{3}}+\sqrt{13-4\sqrt{3}}\)

=\(\sqrt{\left(\sqrt{3}-1\right)^2}+\sqrt{\left(2\sqrt{3}-1\right)^2}\)

=\(|\sqrt{3}-1|\)+\(|2\sqrt{3}-1|\)

= \(\sqrt{3}-1+2\sqrt{3}-1\)

=\(3\sqrt{3}-2\)


Các câu hỏi tương tự
Khùng Điên
Xem chi tiết
Không Biết
Xem chi tiết
Phạm Minh Hiền
Xem chi tiết
Nguyễn Duy Phương
Xem chi tiết
Trâm Nguyễn Thị Ngọc
Xem chi tiết
Nguyễn Ngọc Nhã Hân
Xem chi tiết
thiên thương nguyễn ngọc
Xem chi tiết
Ngoc Tran
Xem chi tiết
WW
Xem chi tiết